Necrotizing Enterocolitis’ In Premature Neonates - The Putative Role of Early Gastrointestinal Colonization - K, Dr. Raksha; Baliga, Dr. Shrikala (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Necrotizing enterocolitis (NEC) is a gastrointestinal emergency and a major cause of morbidity in the neonatal intensive care unit (NICU).We studied the risk factors, pattern and type of microorganisms colonizing the gastrointestinal tract of neonates with NEC, their antibiotic susceptibility and its role in NEC. Material and methods: 40 neonates were included in our prospective case control study over 15 months, 18 with NEC and 22 with no NEC. Risk factors for NEC were assessed. Oral and rectal swabs collected on day 1, day 3 & day 7 and processed. Antibiotic susceptibility testing was performed on the isolates based on CLSI guidelines. Results and conclusion: Of neonates with NEC 100 % were preterm, delivered by lower segment Caesarean section and on parenteral nutrition, 44 % were of low birth weight, 56 % of very low birth weight, 89 % were given formula feeds and none were colonized on day 1. Klebsiella sp., Enterobacter sp., Acinetobacter sp. and S. aureus were isolated relatively more from neonates with NEC. Resistance to antibiotics used for treatment- ampicillin (52-57%), gentamicin (31-82%), cefotaxime (43-80%) for NEC was found. Risk factor association and change in antibiotic resistance prevalence was statistically significant. Delayed colonization, also pathogenic strains were seen to be associated with NEC in premature infants in the NICU. Acquisition of these nosocomial and resistant pathogens as flora in the NICU is an issue of concern.